Pengaruh Konseling terhadap Keikutsertaan Konseling KB Pasca Salin di Puskesmas Sedayu II - Rohani Widiyanti; Juda Julia Kristiarini; Siti Maimunah (Malahayati Nursing Journal, 2024)
ABSTRACT Family planning counseling in daily services is routinely carried out, but the reality on the ground is that there are still many mothers who do not use contraception until they are fertile again. The family support team has the task of visiting postpartum mothers and providing counseling to ensure that every postpartum mother uses contraception. Many factors influence an acceptor's interest in using contraception. Sedayu II Health Center is a health center with low postpartum family planning coverage, namely 15.6%. The purpose of conducting this study was to analyzing the influence of the Family Assistance Team's family planning counseling on postnatal family planning participation in the Sedayu II Community Health Center working area. The research used a pre-experimental design and was carried out in March 2024 for one week. The research involved 34 postpartum mothers at the Sedayu II Community Health Center, sampling using the accidental sampling technique. The data collection tool uses a questionnaire containing a list of questions about family planning approval, family planning counseling, and the Family Assistance Team. This research uses univariate data analysis with frequency distribution and bivariate analysis with Wilcoxon. Most of the respondents were aged 20–35 years (79.4%), had higher education (73.5%), had a job (67.6%), and had parity ≤2 children (70.6%). Respondents who wanted to take part in a family planning program before being given counseling were 8.8%, and respondents who wanted to use contraception after being given counseling were 100%. Using Wilcoxon analysis, it was concluded that there was a significant influence on participation in post-natal family planning between pre and post, with a P value of 0.000. From the results of this research, it can be concluded that there is an influence of postpartum family planning counseling on interest in participating in postpartum family planning by the Family Assistance Team at the Sedayu II Community Health Center. Keywords: Assistance, Counseling, Family Planning, Motherhood, Postpartum  ABSTRAK Konseling KB dalam pelayanan sehari - hari sudah rutin dilakukan, namun kenyataan di lapangan, masih banyak ibu yang tidak menggunakan kontrasepsi hingga masa suburnya kembali. Tim pendamping keluarga mempunyai tugas untuk mengunjungi ibu pasca salin dengan perannya memberikan konseling untuk memastikan setiap ibu pasca salin memakai kontrasepsi. Banyak faktor yang mempengaruhi minat seorang aseptor untuk memakai alat kontrasepsi. Puskesmas Sedayu II merupakan puskesmas dengan cakupan KB pasca salin yang rendah yaitu 15,6%. Tujuan dilakukakan penelitian ini untuk menganalisa pengaruh konseling KB Tim Pendamping Keluarga terhadap keikutsertaan KB pasca salin di wilayah kerja Puskesmas Sedayu II. Penelitian menggunakan desain pre-eksperimen dan dilaksanakan pada bulan Maret 2024 selama 1 minggu. Penelitian melibatkan 34 ibu pasca salin di Puskesmas Sedayu II, pengambilan sampel menggunakan teknik accidental sampling. Alat pengumpulan data menggunakan kuesioner yang berisi daftar pertanyaan tentang persetujuan KB, konseling KB dan Tim Pendamping Keluarga. Penelitian ini menggunakan analisis data univariat dengan distribusi frekuensi dan analisis bivariat dengan Wilcoxon. Hasil penelitian ini, sebagian besar responden berusia 20-35 tahun (79,4%), berpendidikan tinggi (73,5%), mempunyai pekerjaan (67,6%), mempunyai paritas ≤2 anak (70,6%), responden yang mau ikut dalam program KB sebelum diberikan konseling sebesar (8,8%) dan responden yang mau memakai kontrasepsi setelah diberikan konseling sebesar 100%. Pengaruh perbedaan antara pre dan post dengan analisis wilcoxon, disimpulkan bahwa terdapat pengaruh yang signifikan terhadap keikutsertaan KB pasca salin antara pre dan post dengan nilai P=0.000. Dari hasil penelitian tersebut, dapat dismpulkan ada pengaruh konseling KB Tim Pendamping Keluarga terhadap keikutsertaan KB pasca salin  di Puskesmas Sedayu II. Kata Kunci: Keluarga Berencana, Konseling, Pasca Persalinan